(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article analyzes the role and reveals the importance of digitization in the activities of executive authorities in providing administrative services to natural persons-entrepreneurs in today’s conditions. The trend and direction of the implementation of digitalization in the activities of executive authorities regarding the provision of administrative services to natural persons- entrepreneurs have been analyzed. The advantages and disadvantages of the implementation of digitization are listed. It has been established that, as of today, digitalization in the activities of executive authorities regarding the provision of administrative services to natural persons-entrepreneurs is mainly of an innovative nature, however, both applied and theoretical, as well as a legislative basis can be seen for the Ukrainian state to strengthen its position at the level of development of information and communication technologies and network economy among other countries of the world.